2022
DOI: 10.3390/microorganisms10020252
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Susceptibility Profile and Whole-Genome Analysis of a Strong Biofilm-Forming Bacillus Sp. B87 Strain Isolated from Food

Abstract: Members of the Bacillus cereus group are considered to be foodborne pathogens commonly associated with diarrheal and emetic gastrointestinal syndromes. Biofilm formation is a major virulence determinant of various pathogenic bacteria, including the B. cereus strains, since it can protect the bacteria against antimicrobial agents and the host immune response. Moreover, a biofilm allows the exchange of genetic material, such as antimicrobial resistance genes, among the different bacterial strains inside the matr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 67 publications
(76 reference statements)
0
11
1
Order By: Relevance
“…Moreover, several previous studies emphasized the resistance of B. cereus to β-Lactam -β-lactamase-inhibitor combination. 19,89,90 In contrast to our findings, Chen 91 reported an impairment of bla1 transcription in B. cereus group that harbored bla promoter-lacZ transcriptional fusions and attributed that to the betagalactosidase activity of the group.…”
Section: Discussioncontrasting
confidence: 99%
“…Moreover, several previous studies emphasized the resistance of B. cereus to β-Lactam -β-lactamase-inhibitor combination. 19,89,90 In contrast to our findings, Chen 91 reported an impairment of bla1 transcription in B. cereus group that harbored bla promoter-lacZ transcriptional fusions and attributed that to the betagalactosidase activity of the group.…”
Section: Discussioncontrasting
confidence: 99%
“…MKAL5 displayed moderate ability. Many investigators revealed the biofilm-forming ability of these bacteria species [Esteban and García-Coca, 2018;Kim et al, 2020;Bostanghadiri et al, 2021;Sornchuer et al, 2022]. Bacillus sp.…”
Section: Discussionmentioning
confidence: 99%
“…Bacillus species can also be used as a bacterial concentrate to reduce odors and kill pathogenic bacteria, as well as potential as probiotics (Łubkowska et al 2023). However, Bacillus cereus is also considered a foodborne pathogen that commonly causes gastrointestinal diarrhea and emetics (Sornchuer et al 2022). Bacillus cereus originating from soil can cause food poisoning because this bacterium is an enteropathogenic strain that produces enterotoxins in the intestine (Jessberger et al 2020).…”
Section: Discussionmentioning
confidence: 99%